An investigation of construction of chondroitin sulfate E (CS-E) repeating unit. Issue 37 (15th September 2016) - Yang, Shuang; Wang, A-peng; Zhang, Guangyan; Di, Xiangjie; Zhao, Zhehui; Lei, Pingsheng
Abstract: A series of the derivatives of chondroitin sulfate E (CS-E) disaccharide repeating unit were prepared by postglycosylation–oxidation strategy. The strategy showed excellent performance in glycosylation both on the reactivity and stereoselectivity. Different protecting methodologies were used for the manipulation of disaccharide building blocks. Substitutes at C-4 of glucosyl donors mildly influenced the glycosylation. The current synthesis afforded a feasible approach for the preparation of CS-E repeating unit. Graphical abstract: